Exploring the Relationship Between Palatal Cleft Type and Width With the Use of Relieving Incisions in Primary Repair. (May 2022) - Davies, Alex; Davies, Amy; Wren, Yvonne; Deacon, Scott; Cobb, Alistair R.M.; Chummun, Shaheel
Objective: The mainstay of palatal repair in the United Kingdom is the intravelar veloplasty (IVVP). It is not always possible to align the oral mucosa in the midline to achieve tension-free repair. The addition of lateral relieving incisions may aid transposition of the oral mucosa to allow closure. The aim of this study was to explore cleft features that may predispose to a requirement for relieving incisions in order to allow palate closure. Design: We performed a national multiinstitutional retrospective study using data from the UK Cleft Collective cohort study. Patients: The study sample consisted of 474 patients who had undergone IVVP at the time of palatal closure across all 16 of the UK cleft units. Results: We found strong evidence for the requirement for relieving incisions in patients with an increased degree of clefting per the Veau classification ( P < .001), increasing palatal soft-edge width ( P < .001) and moderate evidence of an associated use in patients with Pierre Robin sequence ( P = .015). Insufficient data were available to explore the relationship between intertuberosity distance and the presence of fistula formation with the use of relieving incisions. Conclusions: The results of this study identify cleft features that increase the likelihood for requiring lateral relieving incisions to allow palatal closure. The degree to which the addition of relieving incisions to IVVP affects maxillary growth and speech outcomes is unknown. Further study is required to answer this important question.